Психофізична готовність майбутніх офіцерів-правоохоронців до службово-бойової (оперативної) діяльності - Гіренко, С. П.; Girenko, S. P.; Голубничий, М. В.; Holubnychyi, M. V.; Тулінов, В. С.; Tulinov, V. S.; Коваленко, В. Л.; Kovalenko, V. L.; Пащенко, В. М.; Pashchenko, V. M.; Стасенко, О. А.; Stasenko, O. A.; et al. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2023. - Вип. 2(160). - С. 81-86, 2023)
Досліджено екстремальні фактори, які впливають на психофізичну готовність майбутніх офіцерів-правоохоронців під час виконання ними завдань за призначенням. Визначено ефективні педагогічні моделі, технології, методики, які забезпечують готовність майбутніх офіцерів інституцій сектору безпеки і оборони України до професійної діяльності із акцентованим використанням засобів фізичної, та спеціальної фізичної підготовки.

Taking into account the results of the monitoring of scientific and methodological, special and reference literature, the members of the scientific research group determined that the actual issue of determining the components that affect the psychophysical readiness of future officers of the institutions of the security and defense sector of Ukraine with law enforcement functions for service and combat (operational) activities -dedicated to the insufficient number of studies, this in turn emphasizes the relevance and practical component of the chosen direction of scientific research.The main goal of the study is to determine the extreme factors that affect the psychophysical readiness of future law enforcement officers during their assigned tasks. Research methods: abstraction, measurement, expert evaluation, survey, comparison, observation, etc.As a result of a theoretical study, the members of the scientific research group identified extreme factors that affect the psychophysical readiness of future law enforcement officers during their assigned tasks. In our opinion, the structure of the influence of extreme factors on the psychophysical readiness of representatives of the studied category during their performance of official duties in primary officer positions is: 1) motivation to perform service-combat (operational) activities in extreme conditions (with corresponding dependencies: psychological state of the individual; physical condition; adaptation; adaptation reactions; effectiveness of performing assigned tasks; level of professional competence formation, etc.); 2) nature of extreme factors (block 1: disruption of tissue structure, inhibition of enzyme activity, disruption of oxidative processes, intracellular acidosis, cell hypoxia, glycolysis, regeneration, physiological responses; block 2:mechanical; physical; chemical, thermal, biological, social, anthropogenic (pathogenic), material and technical; block 3: violation of the process of processing (perception) of information, impulsiveness in actions, inhibition, violation of executive functions, violation of the process of perception and thinking, emotional stress, psychological (psychophysical) reactions of responses);3) readiness stressors (combat danger, hypodynamia (hypokinesia), vibration (shaking), pathogenic microorganisms, physical(psychophysical) stress, neuropsychological stress, pain, cold, hypoxia, heat, thirst).Prospects for further research in the chosen direction of scientific research include the development of applied physical exercise complexes that involve the use of TRX loops in the system of individual physical training of future officers of institutions of the security and defense sector of Ukraine.

Исследованы экстремальные факторы, влияющие на психофизическую готовность будущих офицеров-стражей порядка во время выполнения ими задач по назначению. Определены эффективные педагогические модели, технологии, методики, обеспечивающие готовность будущих офицеров институтов сектора безопасности и обороны Украины к профессиональной деятельности с акцентированным использованием средств физической и специальной физической подготовки.
Psychophysical readiness of future law enforcement officers for service - combat (operational) activity
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; майбутні офіцери-правоохоронці; future law enforcement officers; будущие офицеры-правоохранители; професійна освіта; professional education; профессиональное образование; психофізична готовність; psychophysical readiness; психофизическая готовность; спеціальна фізична підготовка; special physical training; специальная физическая подготовка; екстремальні фактори; extreme factors; экстремальные факторы